treeducken: An R package for simulating cophylogenetic systems - Wade Dismukes; Tracy A. Heath (Methods in Ecology and Evolution)
Abstract Cophylogenetic methods describe discordance between non‐independent phylogenies. Simulation is necessary for testing cophylogenetic methods, but few simulators exist that are capable of generating data under explicit and biologically meaningful models. We present an R package, treeducken, for simulating host–symbiont evolution and gene‐tree–species‐tree evolution. treeducken provides a straightforward and reproducible interface for simulating cophylogenetic data. This allows easier performance testing of methods and has potential applications in machine learning (ML) and approximate Bayesian computation (ABC) approaches.